CATATAN TENTANG TOL LAUT JOKOWI - Budi Santoso; Harun Umar (Universitas Nasional, 2018)
A note on Tol Laut Jokowi is presented covering the economic potensial of the sea, maritime security history of Indoensian Maritime in brief. Overlapping of authorizations in the sea manajerial usies by the government institutions namely : Bakamla, Maritime ministry and Fisheries, Navy, and the state police should not create conflict of interest if they can be coordinated signergitically diplomatic concerns should be taken cares related to the China’s concept on South China Sea, in prospect of UNCLOS.